ANALISIS VOLATILITAS PASAR MODAL DI INDONESIA PENERAPAN MODEL GARCH PADA RETURN SAHAM IHSG HARIAN 4 APRIL 1983 â 15 JULI 2013 - , ANDREAS KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Several studies related to stock market return volatility have been performed by researchers, from linear model which assume constant variance to nonlinear model with structural breaks such as Markov-switching. This study aims to analyse daily stock market return volatility in Indonesia period April 4 th 1983 â July 15 th 2013 using Autoregressive Conditional Heteroscedasticity (ARCH), Generalized Autoregressive Conditional Heteroscedasticity (GARCH), and its leverage. Estimation results found linear model, which assume constant variance, no longer accurate to predict stock market return volatility movement in Indonesia. Good news and bad news also give different impact to volatility.